2017
DOI: 10.3389/fncir.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Color Representation Is Retinotopically Biased but Locally Intermingled in Mouse V1

Abstract: Dichromatic vision is common in many mammals. However, color processing in the primary visual cortex (V1) of dichromatic mammals is relatively unknown compared to the trichromatic primates. In this study, we investigated the functional organization of color processing in mouse V1. The mouse retina has a graded expression pattern of two opsins along its dorsoventral axis. However, it is not clear whether and how this expression pattern is reflected in the cortical representation at local (several hundred micron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…By projecting 29 the spatial profile of cones into visuotopic coordinates based on the mean eye position during our experiments (Figure 1 – figure supplement 1), we computed expected middle/short ratios for each of the elevations we tested (Figure 3 – figure supplement 1). Similar to the estimated relative opsin weights across V1 under photopic conditions 23,37 , 2.3, 0.81, 0.81, the cone functional distribution predicts 2.3, 1.0, and 0.44 at –10°, 10°, and 30°, respectively; both predict far less middle-band sensitivity that we observed. This result suggests that rod opsin sensitivity contributes significantly to mouse perceptual sensitivity at these light levels, at least as much as 60% (Figure 3 – figure supplement 1) at higher elevations.…”
Section: Resultssupporting
confidence: 75%
“…By projecting 29 the spatial profile of cones into visuotopic coordinates based on the mean eye position during our experiments (Figure 1 – figure supplement 1), we computed expected middle/short ratios for each of the elevations we tested (Figure 3 – figure supplement 1). Similar to the estimated relative opsin weights across V1 under photopic conditions 23,37 , 2.3, 0.81, 0.81, the cone functional distribution predicts 2.3, 1.0, and 0.44 at –10°, 10°, and 30°, respectively; both predict far less middle-band sensitivity that we observed. This result suggests that rod opsin sensitivity contributes significantly to mouse perceptual sensitivity at these light levels, at least as much as 60% (Figure 3 – figure supplement 1) at higher elevations.…”
Section: Resultssupporting
confidence: 75%
“…Several recent studies have found similar mesoscale organization in other response properties in mouse visual cortex. For example, recent studies have found retinotopic asymmetry of color selectivity within area V1 61 and binocular disparity preference within area RL 52 . Moreover, researchers also found that neurons in higher visual and parietal regions exhibit anatomical gradients of task-modulated responses during navigation in a virtual environment, and that these gradients cross retinotopic borders 62 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have found retinotopic asymmetry of color selectivity within area V1 [61] and binocular disparity preference within area RL [52]. Moreover, researchers also found that neurons in higher visual and parietal regions exhibit anatomical gradients of task-modulated responses during navigation in a virtual environment, and that these gradients cross retinotopic borders [62].…”
Section: Implications For Organizational Principles Of Cortical Procementioning
confidence: 97%